Attitudes, self-efficacy, and practices related to opioid risk assessment and mitigation: A comparison of health care professionals in rural communities. Issue 1 (1st December 2022) - Baylis, Jacob D.; Charron, Elizabeth; Archer, Shayla; Garets, Mitchell; Bryan, M. Aryana; Foringer, Jacob; Kelley, A. Taylor; Smid, Marcela C.; Cochran, Gerald
Abstract: Background: Health care professionals (HCPs) play an important role in opioid misuse and opioid use disorder (OUD) screening/identification, mitigation, and referral to treatment. This study compared attitudes, self-efficacy, and practices related to opioid risk assessment and mitigation among pregnancy and non-pregnancy HCPs in rural communities. Methods: We conducted a secondary analysis of cross-sectional, self-report survey data of HCPs in two rural counties in southern Utah. Pregnancy HCPs were identified by a question asking whether they provide care to pregnant patients. HCPs' attitudes toward their patients with opioid misuse/OUD were measured using the Survey of Attitudes and Perceptions questionnaire. Self-efficacy and practices related to opioid risk assessment and mitigation were captured with questions asking about assessment and screening of opioid use, advisement to change opioid use behavior, and referral to treatment for OUD. We used linear regression analyses to estimate associations between HCPs' attitudes toward patients with opioid misuse/OUD and their self-efficacy and use of opioid risk assessment and mitigation practices. Results: This sample included a total of 132 HCPs, including 82 pregnancy HCPs and 50 non-pregnancy HCPs. Attitudes domains were similar among pregnancy and non-pregnancy HCPs. Among pregnancy HCPs, role adequacy ( β = .48, 95% CI = .16–.80), role legitimacy ( β = .72, 95% CI = .21–1.22), motivation ( β = .68, 95% CI = .14–1.21), and positive task-specific self-esteem ( β  = 1.52, 95% CI = .70–2.35) were positively associated with more frequent use of opioid risk assessment and mitigation practices, while attitudes were not associated with these practices among non-pregnancy HCPs. Conclusions: Training initiatives that lead to improved HCP attitudes could improve opioid care management among rural pregnancy HCPs. More research is needed to determine approaches to increase the use of opioid risk assessment and mitigation practices among rural non-pregnancy HCPs.